2010
DOI: 10.1371/journal.pone.0010463
|View full text |Cite
|
Sign up to set email alerts
|

The Increase of Lactobacillus Species in the Gut Flora of Newborn Broiler Chicks and Ducks Is Associated with Weight Gain

Abstract: BackgroundA bacterial role in the obesity pandemic has been suspected based on the ingestion of probiotics that can modify the gut flora. The objective of our study was to determine if increased Lactobacillus sp. in the gut flora of newborn broiler chicks and ducks could result in weight gain increase.MethodologyFemale broiler chicks (Gallus gallus domesticus) and ducks (Anas platyrhynchos domestica) were separated into one control and two experimental groups, and inoculated once or twice with 4×1010 Lactobaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(96 citation statements)
references
References 32 publications
6
88
1
1
Order By: Relevance
“…Compared with the PFE group, the BFE group showed increases in duodenal Lactobacillus (P = 0.002, FDR = 0.162) and cecal Lactobacillus delbrueckii and Lactobacillus reuteri (FDR < 0.05) in the current study. Previous studies suggested that some species of Lactobacillus are associated with weight gain in human and animal infants [37][38][39] . Nevertheless, the body weight of the BFE group was not significantly higher than that of the PFE group, which was not consistent with the statement by Million 40 that Lactobacillus would lead to obesity or weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the PFE group, the BFE group showed increases in duodenal Lactobacillus (P = 0.002, FDR = 0.162) and cecal Lactobacillus delbrueckii and Lactobacillus reuteri (FDR < 0.05) in the current study. Previous studies suggested that some species of Lactobacillus are associated with weight gain in human and animal infants [37][38][39] . Nevertheless, the body weight of the BFE group was not significantly higher than that of the PFE group, which was not consistent with the statement by Million 40 that Lactobacillus would lead to obesity or weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a decrease in numbers of L. salivarius bacteria has been linked with improved broiler performance (14,24,26). However, some probiotics containing either multiple bacterial species or a single bacterial species, including lactobacilli, have been shown to improve feed efficiency and weight gain in chickens (2,38,39), suggesting that perhaps strain-specific characteristics and/or host selective pressures determining the process of colonization (34,62) could influence performance outcomes.…”
Section: Vol 77 2011mentioning
confidence: 99%
“…Furthermore, a positive effect on weight gain has been reported in rapidly growing animals [3], which could be associated with the metabolic effects of probiotics [4]. Some authors have even suggested that there might be a relationship between the composition of the gut microflora and a later risk of obesity in adults [5].…”
Section: Introductionmentioning
confidence: 99%